An InDel insertion in the promoter of a UDP-ᴅ-glucuronate 4-epimerase 1 gene enhances maize resistance to Fusarium ear rot - Dong, Chaopei; Wu, Yabin; Gao, Jingyang; Song, Yunxia; Wu, Zhaokun; Wang, Zhao; He, Jianju; Yu, Qian; Zhao, Zhonghuan; Cao, Mengya; Zhang, Ronghui; Song, Weibin; et al. (Elsevier Inc., 2025)
Fusarium ear rot (FER), caused by Fusarium verticillioides, results in substantial yield losses and poses a significant threat to maize production worldwide. However, the genetic basis of FER resistance remains poorly understood. Utilizing QTL-seq and association analysis, we identified a gene encoding UDP-ᴅ-glucuronate 4-epimerase 1 (ZmGAE1). A 141-base pair insertion was revealed as the natural functional variation in the promoter of ZmGAE1, which decreases its expression and enhances resistance to FER. Functional validation confirmed that ZmGAE1 acts as a negative regulator of maize resistance to FER. Notably, reduced ZmGAE1 accumulation not only improved FER resistance but also lowered fumonisin content. This effect was attributed to increased cell density within the down-placenta chalaza region, accompanied by the accumulation of galacturonic acid and pectin. Crucially, lines lacking ZmGAE1 exhibited no adverse effects on key agronomic traits and showed resistance to multiple diseases, including maize stalk rot, southern leaf blight, and seed rot. These findings highlight ZmGAE1 as a promising candidate for improving FER resistance in maize, offering a novel approach for crop protection and sustainable agriculture.